1995
DOI: 10.1074/jbc.270.12.6496
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific DNA Recognition by the SmaI Endonuclease

Abstract: SmaI endonuclease recognizes and cleaves the sequence CCC decreases GGG. The enzyme requires magnesium for catalysis; however, equilibrium binding assays revealed that the enzyme binds specifically to DNA in the absence of magnesium. A specific association constant of 0.9 x 10(8) M-1 was determined for SmaI binding to a 22-base duplex oligonucleotide. Furthermore, the KA was a function of the length of the DNA substrate and the enzyme exhibited an affinity of 1.2 x 10(9) M-1 for a 195-base pair fragment and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…DNA binding assays were carried out by using duplex, synthetic oligonucleotide substrates. The complementary oligonucleotides were annealed, 5Ј-end-labeled with T4 polynucleotide kinase (New England Biolabs), and purified as previously described (68). Experiments used crude extracts containing equivalent concentrations of C ⅐ PvuII FLAG fusion proteins, as determined by Western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…DNA binding assays were carried out by using duplex, synthetic oligonucleotide substrates. The complementary oligonucleotides were annealed, 5Ј-end-labeled with T4 polynucleotide kinase (New England Biolabs), and purified as previously described (68). Experiments used crude extracts containing equivalent concentrations of C ⅐ PvuII FLAG fusion proteins, as determined by Western blot analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Note that only a subset of restriction enzymes is able to bind to the correct sequence in the absence of divalent metal ions. Some of these are SmaI and EcoRI, for which the specific and nonspecific binding constants have been determined (12,15). Kinetic tests of -DNA restriction by SmaI using a moving Mg 2ϩ front inside a microchannel has confirmed that the cutting occurs on a time scale shorter than 4 s with our combination of buffer and enzyme concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The restriction enzymes (New England Biolabs) were used with concentrations of Ϸ3 nM for SmaI, Ϸ3 nM for SacI, and Ϸ13 nM for PacI. We chose these concentrations because of the specific binding constant for SmaI of Ϸ10 9 M Ϫ1 (12). The solution that was filled into the ''entry''-Freely available online through the PNAS open access option.…”
Section: Methodsmentioning
confidence: 99%
“…What are the features of SmaI and PvuII interaction with DNA that make them respond differently than other restriction endonucleases tested for inhibition by THPs? Withers and Dunbar (50) noticed that PvuII displays certain similarities with SmaI, such as (i) interaction with each of the base pairs within the recognition site, (ii) a potential protein contact to the phosphate 3Ј to the scissile bond, and (iii) no significant bending of the DNA. In addition, SmaI interactions with DNA phosphates are all adjacent and clustered within the recognition site (50), whereas EcoRV endonuclease exhibit phosphate interactions both within and flanking the recognition sequence (51).…”
Section: Discussionmentioning
confidence: 99%
“…Withers and Dunbar (50) noticed that PvuII displays certain similarities with SmaI, such as (i) interaction with each of the base pairs within the recognition site, (ii) a potential protein contact to the phosphate 3Ј to the scissile bond, and (iii) no significant bending of the DNA. In addition, SmaI interactions with DNA phosphates are all adjacent and clustered within the recognition site (50), whereas EcoRV endonuclease exhibit phosphate interactions both within and flanking the recognition sequence (51). In EcoRI, DNA phosphate interactions are delocalized, so the primary clamp occurs at the immediate 5Ј-end of the recognition sequence, and supplementary clamps occur adjacent to the primary and at the center of the recognition sequence (52).…”
Section: Discussionmentioning
confidence: 99%